Pengaruh Online Review pada Online Travel Agent Traveloka terhadap Niat Pemesanan Hotel di Aston Pasteur Bandung - Andiza, Muhammad Rafi; Kusumah, Ahmad Hudaiby Galih (Tourism and Hospitality Essentials Journal, 2023)
Online reviews are a significant source of information for consumers to investigate the influence of online hotel purchasing decisions. In this context, Traveloka OTA has become a popular platform in Indonesia that provides online reviews to help consumers choose hotels. This study used a quantitative approach using a questionnaire with 200 respondents as a data collection instrument. The research sample consisted of consumers who had made hotel reservations through OTA Traveloka at ASTON Pasteur Bandung. The collected data were analyzed using regression analysis techniques to determine the relationship between online review variables and hotel booking intentions. The results of the study show that online reviews on Traveloka OTA have a significant influence on hotel booking intentions. Factors such as usefulness of online reviews, review expertise, timeliness of online reviews, volume of online reviews, positive of online reviews, negative of online reviews, and comprehensiveness of online reviews play an important role in influencing hotel booking intentions. This research contributes to expanding understanding of the effect of online reviews on Traveloka OTA on hotel booking intentions at ASTON Pasteur Bandung. The results of this study can provide implications and insights for hotels and OTAs in optimizing the use of online reviews as an effective marketing tool. In addition, this research also provides benefits for consumers in choosing hotels that suit their preferences and needs